MS-150-10-f02-010: Letter from Connemara - Connemara, Lord, 1827-1902 (Valdosta, GA: Valdosta State University Archives and Special Collections, 1897)
Letter from [Lord] Connemara [Robert Bourke], dated May 23, [no year]. Inviting Arnold to dinner with Indian friends
1 handwritten letter, 2 pages.
Keywords: Personal correspondence; Letters; Arnold, Edwin, Sir, 1832-1904; Poets--Correspondence; Nobility--England--Correspondence